Implementation of Marker Based Tracking Method in the Interactive Media of Traditional Clothes Knowledge-Based on Augmented Reality 360 - Okvi Nugroho (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2020)
Knowledge of traditional clothes, especially Indonesia, is currently carried out using digital media such as radio, television and the museum's official website. The limitation of presenting museum information in Indonesia makes the delivery of visual information not yet optimal Studies prove by combining several senses at once in presenting a content can increase people's memory and interest in the content. One of the technologies related to multimedia is Augmented Reality. In this study the authors built an Augmented Reality 360 Interactive Application on Custom Clothing Using a Marker Based Tracking Method that aims to introduce traditional clothes to the Museum used as objects to provide information to the public about traditional clothes with Augmented reality technology and Conveying information for the introduction of traditional clothes. Augmented reality applications on traditional clothes are built using 3D unity software and using Vuforia in applying the marked based tracking method in retrieving a database of images on a marker. The results of this research are applications that can display traditional clothes using augmented reality-based technology so that they are easy to use by the wider community such as the general public and students.